Compositions, adhesives and joints

JP7642085B2Active Publication Date: 2025-03-07DENKA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023551458
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-29
Filing Date
2022-09-26
Publication Date
2025-03-07
Estimated Expiration
2042-09-26

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、速硬化性及び耐ヒートサイクル性に優れた接着剤に利用可能な組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642085000001
    Figure 0007642085000001
  • Figure 0007642085000002
    Figure 0007642085000002
  • Figure 0007642085000003
    Figure 0007642085000003
Patent Text Reader

Abstract

Provided is a composition that can be used for an adhesive having excellent fast curability and heat cycle resistance. The present invention provides a two-agent type composition comprising a first agent and a second agent. The first agent contains an elastomer (A), a first acrylic component (B), a second acrylic component (C), and a polymerization initiator (D). The second agent contains a condensate (E) of an aldehyde and an amine, a third acrylic component (F), and a reducing agent (G). The first acrylic component (B) is a (meth)acrylate or a (meth)acrylic acid including, in one molecule thereof, two or more hydroxyl groups bound to carbon atoms or including, in one molecule thereof, one or more of at least one type of a functional group selected from the group consisting of an amide group, a cyclic amide group, a sulfoxide group, a ketone group, an aldehyde group, a sulfo group, a sulfino group, a phosphone group, a sulfobetaine group, a carbobetaine group, and a phosphobetaine group. The second acrylic component (C) is a (meth)acrylate or a (meth)acrylic acid other than the first acrylic component (B). The third acrylic component (F) is a (meth)acrylate or a (meth)acrylic acid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to compositions, adhesives and joints. [Background technology]

[0002] There is an increasing demand for adhesives that cure in a short time at room temperature in order to improve production line efficiency and reduce costs. Well-known room temperature fast-curing adhesives include two-part fast-curing epoxy adhesives, instant adhesives, anaerobic adhesives, non-anaerobic acrylic adhesives, etc.

[0003] Two-part fast-curing epoxy adhesives are used by measuring and mixing the base agent and the curing agent, and if the measuring and mixing are not done properly, there is a risk of a significant decrease in strength. Even if the measuring and mixing are done properly, there is also the problem of low peel strength and impact strength.

[0004] On the other hand, instant adhesives have excellent workability, but generally have low peel strength, low impact strength, and poor heat resistance and moisture resistance, which severely limits the range of use.

[0005] On the other hand, anaerobic adhesives are adhesives that cure by pressing the adhesive between the materials to be bonded to block air, so naturally, the adhesive does not cure in areas that come into contact with air, such as protruding areas. Therefore, when the adherend is porous or the balance between the adherends is poor, the adhesive does not cure sufficiently, resulting in poor adhesion.

[0006] In contrast, non-anaerobic acrylic adhesives, generally known as second generation acrylic adhesives (SGA), are two-component adhesives, but do not require precise measurement of the two components; they have excellent workability as they can be roughly measured and mixed and harden in a few minutes to a few tens of minutes at room temperature. In addition, they have high peel strength and impact strength, and harden well in any protruding areas, which is why they have become widely used.

[0007] For example, Patent Document 1 reports that by controlling the content of acrylonitrile monomer units in 100 parts by mass of a nitrile-butadiene rubber component to 5 to 30 parts by mass, durability can be improved and corrosion reactions such as oxidation of the adherend can be prevented when the adherend is made of metal such as copper, thereby achieving even higher adhesion. In addition, Patent Document 2 reports that the use of a compound having an enal structure and a compound having an amine structure can promote rapid curing of the adhesive, and that the moisture resistance can be improved by controlling the content of acrylonitrile monomer units in 100 parts by mass of the nitrile-butadiene rubber component to 10 to 30 parts by mass. In addition, although it is not a two-component type, Patent Document 3 reports that the adhesive strength of a one-component acrylic adhesive can be improved by using at least one type of oligomer having two or more (meth)acrylic groups in the molecule, and (meth)acrylate-modified liquid rubber is reported as an example of the oligomer. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent Publication 2009-197160 [Patent Document 2] International Publication WO2010 / 041710 [Patent Document 3] Patent Publication No. 2021-123655 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a composition that can be used as an adhesive having excellent fast curing properties and heat cycle resistance. [Means for solving the problem]

[0010] As a result of the investigations conducted by the present inventors, it has been found that a two-part composition is obtained by: a first part containing an elastomer (A), a first acrylic component (B), a second acrylic component (C), and a polymerization initiator (D); a second part containing an amine and aldehyde condensate (E), a third acrylic component (F), and a reducing agent (G); and the first acrylic component (B) contains, in one molecule, two or more hydroxyl groups bonded to a carbon atom, or contains, in one molecule, an amide group, a cyclic amide group, a sulfoxide group, a ketone group, an aldehyde group, a sulfo group, a sulfino group, a phosphonic group, a sulfobe group, a sulfobutene group, a cyclic amide group, a sulfur ... It has been found that by forming a two-part composition in which the first acrylic component (B) is a (meth)acrylate or (meth)acrylic acid containing one or more functional groups selected from the group consisting of a betaine group, a carbobetaine group, and a phosphobetaine group, the second acrylic component (C) is a (meth)acrylate or (meth)acrylic acid other than the first acrylic component (B), and the third acrylic component (F) is a (meth)acrylate or (meth)acrylic acid, when used as an adhesive, it is possible to significantly improve the fast curing properties and heat cycle resistance. That is, the present invention provides: (1) It is composed of a first part and a second part, the first part containing an elastomer (A), a first acrylic component (B), a second acrylic component (C) and a polymerization initiator (D), the second part containing an amine and an aldehyde condensate (E), a third acrylic component (F) and a reducing agent (G), the first acrylic component (B) containing two or more hydroxyl groups bonded to a carbon atom in one molecule, or containing one or more amide groups, cyclic amide groups, sulfoxide groups, ketone groups, aldehyde groups in one molecule. a (meth)acrylate or (meth)acrylic acid containing one or more functional groups selected from the group consisting of a sulfo group, a sulfino group, a phosphonic group, a sulfobetaine group, a carbobetaine group, and a phosphobetaine group, the second acrylic component (C) is a (meth)acrylate or (meth)acrylic acid other than the first acrylic component (B), and the third acrylic component (F) is a (meth)acrylate or (meth)acrylic acid; (2) The composition according to (1), wherein the condensate (E) of an amine and an aldehyde is an aldehyde aniline. (3) The composition according to (1) or (2), wherein the first acrylic component (B) is a (meth)acrylate or (meth)acrylic acid containing, in one molecule, two or more hydroxyl groups bonded to carbon atoms, or containing, in one molecule, one or more functional groups selected from the group consisting of a ketone group, an aldehyde group, a sulfoxide group, a sulfo group, a sulfino group, a sulfobetaine group, a carbobetaine group, a phosphone group, and a phosphobetaine group. (4) The composition according to any one of (1) to (3), wherein the content of the first acrylic component (B) is 10 to 40 parts by mass when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass. (5) The composition according to any one of (1) to (4), wherein the content of the monofunctional (meth)acrylate or (meth)acrylic acid in the first acrylic component (B) and the second acrylic component (C) is 70 to 100 parts by mass when the total amount of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass. (6) The composition according to any one of (1) to (5), wherein the content of the elastomer (A) is 30 to 70 parts by mass when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass. (7) The composition according to any one of (1) to (6), wherein one or more of the elastomer components contained in the elastomer (A) is a liquid elastomer (A1) that is liquid at 23° C. (8) The composition according to any one of (1) to (7), wherein the elastomer (A) contains one or more types of NBR. (9) The composition according to (8), wherein the one or more types of NBR contain two or more types of NBR having different nitrile contents. (10) The composition according to any one of (1) to (9), wherein the nitrile content in the elastomer (A) is 0.001 to 0.300 parts by mass per 100 parts by mass of the elastomer (A). (11) The composition according to any one of (1) to (10), wherein the elastomer (A) contains a core-shell type graft copolymer (A2), and the content of the core-shell type graft copolymer (A2) is 0 to 10 parts by mass when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass. (12) The composition according to any one of (1) to (11), wherein the elastomer (A) contains a (meth)acryloyl-modified elastomer (A3). (13) The composition according to any one of (1) to (12), wherein the first agent has a viscosity at 25°C of 1,000 to 100,000 mPa s. (14) The composition according to any one of (1) to (13), comprising 0.001 to 3 parts by mass of a fluorine-containing (meth)acrylate or a fluorine-containing (meth)acrylic acid (F1) per 100 parts by mass of the third acrylic component (F). (15) The composition according to any one of (1) to (14), wherein the reducing agent (G) is a transition metal salt. (16) The composition according to any one of (1) to (15), further comprising a stabilizer (H) in the second agent. (17) The composition according to (16), wherein the content of the stabilizer (H) is 0.001 to 0.5 parts by mass when the total content of the amine and aldehyde condensate (E), the third acrylic component (F), and the reducing agent (G) is 100 parts by mass. (18) The composition according to (16) or (17), wherein the stabilizer (H) contains a stable radical type compound having a stable radical. (19) The composition according to (18), wherein the stable radical of the stable radical compound is a nitroxide radical. (20) The composition according to (18) or (19), wherein the stable radical compound comprises at least one selected from the group consisting of 1-oxyl-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl. (21) An adhesive comprising the composition according to any one of (1) to (20). (22) An adhesive for a speaker or an adhesive for a motor, comprising the composition according to any one of (1) to (20). (23) A bonded body obtained by bonding using the composition according to any one of (1) to (20). Regarding. Effect of the Invention

[0011] According to the present invention, it is possible to provide a composition that can be used as an adhesive having excellent fast curing properties and heat cycle resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <Terminology explanation> In the present specification, for example, the description "A to B" means A or more and B or less. In this specification, the term "(meth)acrylate or (meth)acrylic acid" includes the case where only (meth)acrylate is contained, the case where only (meth)acrylic acid is contained, and the case where both (meth)acrylate and (meth)acrylic acid are contained. In the present specification, the term "acrylic component" includes a case where only an acrylic component is contained, a case where only a methacrylic component is contained, and a case where both an acrylic component and a methacrylic component are contained.

[0013] Hereinafter, the embodiments of the present invention will be described in detail. The present invention is not limited to these, and various modifications are possible without departing from the spirit of the present invention. The features shown in the following embodiments can be combined with each other. In addition, each feature can be an invention independently.

[0014] <Two-dose composition> The two-part composition according to the present embodiment is composed of a first part and a second part. The first part contains an elastomer (A), a first acrylic component (B), a second acrylic component (C), and a polymerization initiator (D). The second part contains an amine and aldehyde condensate (E), a third acrylic component (F), and a reducing agent (G). The first acrylic component (B) contains, in one molecule, two or more hydroxyl groups bonded to a carbon atom, or contains, in one molecule, an amide group, a cyclic amide group, a sulfoxide group, a ketone group, or a condensate of an amine and an aldehyde (E). the second acrylic component (C) is a (meth)acrylate or (meth)acrylic acid containing one or more functional groups selected from the group consisting of an aldehyde group, a sulfo group, a sulfino group, a phosphonic group (phosphonic acid group), a sulfobetaine group, a carbobetaine group, and a phosphobetaine group; the second acrylic component (C) is a (meth)acrylate or (meth)acrylic acid other than the first acrylic component (B); and the third acrylic component (F) is a (meth)acrylate or (meth)acrylic acid. Hereinafter, each component contained in the first and second agents will be described.

[0015] <Elastomer (A)> The two-part composition according to the present embodiment contains an elastomer (A) in the first part. Examples of the elastomer (A) include various rubbers such as nitrile butadiene rubber (NBR), butadiene rubber, acrylic rubber, and urethane rubber, and graft copolymers such as methyl methacrylate-butadiene-styrene graft copolymer (butadiene / MMA / ST copolymer), (meth)acrylate-butadiene-(meth)acrylonitrile-styrene copolymer, and acrylonitrile-butadiene-styrene graft copolymer. The elastomer (A) according to the present embodiment may be one of these elastomers or a combination of two or more of them.

[0016] In the two-part composition according to the present embodiment, the content of the elastomer (A) is preferably 30 to 70 parts by mass, more preferably 30 to 50 parts by mass, when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass, from the viewpoint of improving heat cycle resistance. The content of the elastomer (A) is specifically, for example, 30, 35, 40, 45, 50, 55, 60, 65, or 70 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here. In addition, when the elastomer (A) is used in combination, the content of the elastomer (A) means the total amount of the elastomer (A) used in combination.

[0017] <Liquid elastomer (A1)> In the two-part composition according to the present embodiment, in consideration of workability (applicability of the adhesive) and from the viewpoint of improving heat cycle resistance, it is preferable that one or more of the elastomers (A) contain a liquid elastomer (A1). Here, "liquid" in the present invention means that it is liquid at room temperature (23°C), and specifically, it is determined to be liquid according to the test of "ASTM D 4359-90: Standard Test Method for Determining Whether a Material is a Liquid or Solid".

[0018] The liquid elastomer (A1) preferably has a viscosity of 100,000 to 400,000 mPa·s, and more preferably 200,000 to 300,000 mPa·s, as measured at 27° C. using a BH type viscometer. Specifically, the viscosity is, for example, 100,000, 150,000, 200,000, 250,000, 300,000, 350,000, or 400,000 mPa·s, and may be within a range between any two of the numerical values ​​exemplified here.

[0019] Examples of the liquid elastomer (A1) according to the present embodiment include liquid nitrile butadiene rubber (NBR) and liquid butadiene rubber (BR). From the viewpoint of toughness, liquid nitrile butadiene rubber (NBR) is preferred. As the liquid elastomer (A1) according to this embodiment, a (meth)acryloyl-modified elastomer (A3) may be used. The liquid elastomer (A1) according to the present embodiment may use these liquid elastomers alone or in combination of two or more kinds.

[0020] An example of the liquid elastomer (A1) that can be mentioned as a commercially available product is "HYPRO (registered trademark) 1300X33LC VTBNX" manufactured by HUNTSMAN.

[0021] In the two-part composition according to the present embodiment, the content of the liquid elastomer (A1) is preferably 1 to 50 parts by mass, more preferably 10 to 40 parts by mass, when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass, from the viewpoint of improving heat cycle resistance. The content of the liquid elastomer (A1) is specifically, for example, 1, 5, 10, 15, 20, 25, 30, 35, 40, or 50 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here. When the liquid elastomer (A1) is used in combination, the content of the liquid elastomer (A1) means the total amount of the liquid elastomer (A1) used in combination. In the two-component composition according to this embodiment, the content of the liquid nitrile butadiene rubber (NBR) is preferably 80 parts by mass or less, and more preferably 30 to 65 parts by mass, in 100 parts by mass of the elastomer (A).

[0022] <Nitrile butadiene rubber (NBR)> The two-component composition according to this embodiment preferably contains nitrile butadiene rubber (NBR) as the elastomer (A). Nitrile butadiene rubber (NBR) is a polymer having (meth)acrylonitrile and 1,3-butadiene as constituent units and having rubber-like elasticity at normal temperature, and can be obtained by copolymerizing butadiene and (meth)acrylonitrile. By containing nitrile butadiene rubber (NBR) in combination with other components, toughness can be expected. Examples of NBR include solid NBR and liquid NBR. Here, the "solid NBR" refers to NBR that does not correspond to the above-mentioned "liquid NBR".

[0023] <Nitrile content of NBR> From the viewpoint of improving heat cycle resistance while considering workability (coating property of the adhesive), the two-component composition according to this embodiment preferably contains two or more types of NBR having different nitrile contents. The nitrile content of NBR is the content (parts by mass) of the (meth)acrylonitrile monomer unit in 100 parts by mass of NBR. From the viewpoint of improving heat cycle resistance, the nitrile content of NBR is preferably 1 to 70 parts by mass, more preferably 15 to 60 parts by mass, in 100 parts by mass of NBR. Specifically, for example, it is 1, 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, or 70 parts by mass, and may be within the range between any two of the values exemplified here.

[0024] When the two-component composition according to this embodiment contains two or more types of NBR having different nitrile contents, from the viewpoint of toughness, the nitrile content of the NBR with a higher nitrile content is preferably 20 to 40 parts by mass, more preferably 30 to 35 parts by mass, in 100 parts by mass of NBR. Also, from the viewpoint of improving heat cycle resistance, the nitrile content of the NBR with a lower nitrile content is preferably 1 to 39 parts by mass, more preferably 15 to 34 parts by mass, in 100 parts by mass of NBR.

[0025] When the two-part composition according to the present embodiment contains two or more types of NBR having different nitrile contents, the difference between the nitrile content of the NBR having the higher nitrile content and the nitrile content of the NBR having the lower nitrile content is preferably 0.1 to 25 parts by mass, and more preferably 10 to 20 parts by mass, per 100 parts by mass of NBR, from the viewpoint of improving heat cycle resistance while taking into account workability (applicability of the adhesive).

[0026] <Nitrile content in elastomer (A)> In the two-part composition according to the present embodiment, the nitrile content in the elastomer (A) is preferably 0.001 to 0.300 parts by mass, more preferably 0.003 to 0.275 parts by mass, per 100 parts by mass of the elastomer (A), from the viewpoint of improving heat cycle resistance while taking into consideration workability (applicability of the adhesive). Specifically, for example, the nitrile content is 0.001, 0.010, 0.100, 0.200, 0.210, 0.220, 0.230, 0.240, 0.250, 0.260, 0.270, 0.280, 0.290, or 0.300 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here. The nitrile content in the elastomer (A) means the acrylonitrile monomer units contained in the elastomer (A). The acrylonitrile monomer units are, for example, those contained in the NBR or MBAS resin in the elastomer (A).

[0027] <Method for measuring nitrile content> In the two-part composition according to this embodiment, the nitrile content in the elastomer (A) can be measured in accordance with JIS K6451-2. Furthermore, whether a composition contains a plurality of types of NBR having different nitrile contents can be confirmed by the compounding ratio of the NBR used.

[0028] The nitrile content can be controlled by adjusting the amounts of acrylonitrile and 1,3-butadiene, which are structural units, in the production of the NBR used.

[0029] <Core-shell type graft copolymer (A2)> From the viewpoint of imparting thixotropy, the two-component composition according to the present embodiment preferably contains a core-shell type graft copolymer (A2). The core-shell type graft copolymer refers to a graft copolymer in which a polymer serving as a shell component is grafted onto a crosslinked rubber serving as a core component.

[0030] <Core Ingredients> Examples of the main component of the crosslinked rubber that is the core component include butadiene rubber, styrene-butadiene rubber, butyl rubber, ethylene-propylene-diene rubber, isobutylene polymer rubber, ethylene-vinyl acetate copolymer rubber, isoprene rubber, chloroprene rubber, and nitrile rubber. Among these, from the viewpoint of flexibility, crosslinked rubbers mainly composed of butadiene and / or crosslinked rubbers mainly composed of styrene-butadiene are preferred. As the crosslinked rubbers mainly composed of butadiene, known butadiene rubbers can be used. As the crosslinked rubbers mainly composed of styrene-butadiene, known styrene-butadiene rubbers can be used. These rubbers may be used alone or in combination of two or more. The core component may contain other optional components within the range that does not impair the effects of the present invention. The content of the optional components is preferably 70 parts by mass or less, more preferably less than 70 parts by mass, more preferably 50 parts by mass or less, and even more preferably less than 50 parts by mass, per 100 parts by mass of the core component.

[0031] <Shell component> The shell component is preferably mainly composed of a homopolymer or copolymer to which one or more monomers selected from the group consisting of (meth)acrylate monomers, (meth)acrylonitrile, and vinyl monomers having a double bond are grafted.

[0032] The (meth)acrylate monomer used in the shell component may be a monofunctional (meth)acrylate, etc. Among these monofunctional (meth)acrylates, alkyl (meth)acrylate is preferred, and methyl (meth)acrylate is more preferred. Examples of vinyl monomers having a double bond used in the shell component include styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, and divinylbenzene. These may be used alone or in combination of two or more. Among these vinyl monomers having a double bond, styrene is preferred.

[0033] Among the shell components, (meth)acrylate monomers are preferred from the viewpoint of swelling degree.

[0034] Examples of the core-shell type graft copolymer (A2) include (meth)acrylate-butadiene-styrene copolymer (hereinafter referred to as MBS resin) obtained by graft copolymerizing (meth)acrylate and, if necessary, styrene as a shell component to a core component that is a crosslinked rubber of butadiene and / or a crosslinked rubber of styrene-butadiene, (meth)acrylate-butadiene-(meth)acrylonitrile-styrene copolymer (hereinafter referred to as MBAS resin) obtained by graft copolymerizing (meth)acrylate and, if necessary, styrene and (meth)acrylonitrile as a shell component to a core component that is a crosslinked rubber of butadiene and / or a crosslinked rubber of styrene-butadiene, and acrylonitrile-butadiene-styrene copolymer (hereinafter referred to as ABS resin) obtained by graft copolymerizing acrylonitrile and styrene as a shell component to a core component that is a crosslinked rubber of butadiene and / or a crosslinked rubber of styrene-butadiene. Among these, MBAS resin is preferable from the viewpoint of toughness and curability. The core-shell type graft copolymer (A2) according to the present embodiment may use these core-shell type graft copolymers (A2) alone or in combination of two or more kinds.

[0035] Examples of MBS resins include Kane Ace B series (manufactured by Kanefuchi Chemical Industry Co., Ltd.), BTA series (manufactured by Rohm and Haas Co., Ltd.), and Metablen series (manufactured by Mitsubishi Rayon Co., Ltd.). Examples of MBAS resins include Denka BL-20 (manufactured by Denka Co., Ltd.). Examples of ABS resins include Denka ABS (manufactured by Denka Co., Ltd.).

[0036] The content ratio of each component in the core-shell type graft copolymer (A2) is preferably 5 to 30 parts by mass of (meth)acrylate, 40 to 80 parts by mass of butadiene, and 10 to 40 parts by mass of other vinyl monomers, more preferably 10 to 25 parts by mass of (meth)acrylate, 40 to 75 parts by mass of butadiene, and 10 to 40 parts by mass of other vinyl monomers, and most preferably 13 to 25 parts by mass of (meth)acrylate, 45 to 75 parts by mass of butadiene, and 0 to 30 parts by mass of other vinyl monomers, in 100 parts by mass of the copolymer (preferably, in the total of 100 parts by mass of (meth)acrylate, butadiene, and other vinyl monomers). The other vinyl monomers refer to monomers other than (meth)acrylate and butadiene. Examples of the other vinyl monomers include (meth)acrylonitrile, styrene, and divinylbenzene. Among these, (meth)acrylonitrile and / or styrene are preferred. When the content ratio of each component in the core-shell type graft copolymer (A2) is within the range of the present invention, toughness can be expected.

[0037] The method for producing the core-shell type graft copolymer (A2) is not particularly limited, and any known technique such as emulsion polymerization using an aqueous dispersion medium and an emulsifier can be used.

[0038] When a radical monomer is used as a constituent of the core component, normal emulsion polymerization can be applied. When a monomer lacking radicals is used, a method of emulsifying and dispersing a prepolymer obtained by ionic polymerization such as cationic polymerization, anionic polymerization, and coordination polymerization in an aqueous dispersion medium can be applied. When producing a particle-type graft copolymer containing multiple polymer components in the same particle, the core component can be produced by a method in which each monomer component is mixed uniformly in advance and then emulsified and dispersed to carry out a reaction, a method in which other components are additionally polymerized (seed polymerization) to a seed particle consisting of a single polymer component, a method in which particles consisting of a single polymer component are mixed together and an acid (hydrochloric acid, etc.) or a salt (sodium sulfate, etc.) is added to cause aggregation and enlargement, etc. In this case, the morphology (phase structure) inside the obtained particle can be controlled by the production method, the ratio of each component, the order of reaction, etc.

[0039] As a method for graft polymerizing the constituent components of the shell component, a method can be applied in which monomers are added to an emulsion dispersion (latex) of the core component in one or multiple stages and polymerized by a radical polymerization technique.

[0040] The emulsion dispersion (latex) of the core-shell type graft copolymer (A2) obtained by the above-mentioned production method can be separated by salting out, recovered and used.

[0041] The content of the core-shell type graft copolymer (A2) is preferably 0 to 10 parts by mass, more preferably 3 to 7 parts by mass, when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass. The content of the core-shell type graft copolymer (A2) is specifically, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here. Within this range, the decrease in heat cycle resistance can be suppressed and thixotropy can be imparted. When the core-shell type graft copolymer (A2) is used in combination, the content of the core-shell type graft copolymer (A2) means the total amount of the core-shell type graft copolymer (A2) used in combination.

[0042] <(Meth)acryloyl-modified elastomer (A3)> From the viewpoint of toughness, the two-part composition according to the present embodiment preferably contains a (meth)acryloyl-modified elastomer (A3). The (meth)acryloyl-modified elastomer (A3) means an elastomer having a (meth)acrylic acid monomer unit. The (meth)acrylic acid monomer unit may be provided in a manner in which the elastomer molecule has a (meth)acryloyl group at its terminal position, or in a manner in which the elastomer molecule has a (meth)acryloyl group in its molecular chain. Preferably, the (meth)acryloyl-modified elastomer has a (meth)acryloyl group at least at its terminal position. Examples of the (meth)acryloyl-modified elastomer (A3) according to the present embodiment include (meth)acryl-terminated NBR, (meth)acryl-terminated polybutadiene, urethane (meth)acrylate, (meth)acryl-terminated silicone oil, etc. From the viewpoint of toughness, (meth)acryl-terminated NBR is preferred. An example of a commercially available product of the (meth)acrylic-terminated NBR is "HYPRO (registered trademark) 1300X33LC VTBNX" manufactured by HUNTSMAN. As the (meth)acryloyl-modified elastomer (A3) according to the present embodiment, these (meth)acryloyl-modified elastomers (A3) may be used alone or in combination of two or more kinds.

[0043] The content of the (meth)acryloyl-modified elastomer (A3) according to the present embodiment is preferably 1 to 40 parts by mass, more preferably 10 to 30 parts by mass, when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass. Specifically, for example, it is 1, 5, 10, 15, 20, 25, or 30 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here. If it is within this range, toughness can be imparted. In addition, when the (meth)acryloyl-modified elastomer (A3) is used in combination, the content of the (meth)acryloyl-modified elastomer means the total amount of the (meth)acryloyl-modified elastomer (A3) used in combination.

[0044] <First acrylic component (B)> The two-part composition according to the present embodiment contains a first acrylic component (B). The first acrylic component (B) is a (meth)acrylate or (meth)acrylic acid that contains, in one molecule, two or more hydroxyl groups bonded to carbon atoms, or contains, in one molecule, one or more functional groups selected from the group consisting of amide groups, cyclic amide groups, sulfoxide groups, ketone groups, aldehyde groups, sulfo groups, sulfino groups, phosphonic acid groups, sulfobetaine groups, carbobetaine groups, and phosphobetaine groups.

[0045] From the viewpoint of curing speed, the first acrylic component (B) according to the present embodiment is preferably a (meth)acrylate or (meth)acrylic acid containing, in one molecule, two or more hydroxyl groups bonded to carbon atoms, or containing one or more functional groups selected from the group consisting of a ketone group, an aldehyde group, a sulfoxide group, a sulfo group, a sulfino group, a sulfobetaine group, a carbobetaine group, a phosphone group, and a phosphobetaine group, and more preferably a (meth)acrylate or (meth)acrylic acid containing, in one molecule, two or more hydroxyl groups bonded to carbon atoms.

[0046] Examples of the first acrylic component (B) according to the present embodiment include glycerin mono(meth)acrylate, maleic anhydride, etc. From the viewpoint of storage stability, glycerin mono(meth)acrylate is preferred. The first acrylic component (B) according to the present embodiment may use these first acrylic components (B) alone or in combination of two or more kinds.

[0047] In terms of curing speed, the content of the first acrylic component (B) according to this embodiment is preferably 10 to 40 parts by mass, more preferably 15 to 30 parts by mass, when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass. Specifically, for example, it is 10, 15, 20, 25, 30, 35, or 40 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here. In addition, when the first acrylic component (B) is used in combination, the content of the first acrylic component (B) means the total amount of the first acrylic component (B) used in combination.

[0048] <Second acrylic component (C)> The two-part composition according to this embodiment contains a second acrylic component (C). In this embodiment, the second acrylic component (C) refers to a second acrylic component (C) that does not correspond to the above-mentioned first acrylic component (B).

[0049] Examples of the second acrylic component (C) according to the present embodiment include (meth)acrylate or (meth)acrylic acid (C1) having one hydroxyl group, (meth)acrylate or (meth)acrylic acid (C2) having a phenyl group, (meth)acrylate or (meth)acrylic acid (C3) having an alkylene oxide or siloxane unit, acyclic polyfunctional (meth)acrylate or (meth)acrylic acid (C4), and phosphoric acid ester compound (C5) having a (meth)acrylic group. From the viewpoints of metal adhesion, solubility of elastomer, curing speed, hardness adjustment, etc., it is preferable to use at least one selected from the group consisting of (meth)acrylate or (meth)acrylic acid (C1) having one hydroxyl group, (meth)acrylate or (meth)acrylic acid (C2) having a phenyl group, and (meth)acrylate or (meth)acrylic acid (C3) having an alkylene oxide or siloxane unit. The second acrylic component (C) according to the present embodiment may use these second acrylic components (C) alone or in combination of two or more kinds.

[0050] <(Meth)acrylate or (meth)acrylic acid (C1) containing one hydroxyl group> Examples of the (meth)acrylate or (meth)acrylic acid (C1) having one hydroxyl group according to this embodiment include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc. From the viewpoint of metal adhesion, 2-hydroxyethyl (meth)acrylate is preferred. The (meth)acrylate or (meth)acrylic acid (C1) according to the present embodiment may be used alone or in combination of two or more kinds.

[0051] <(Meth)acrylate or (meth)acrylic acid having a phenyl group (C2)> Examples of the (meth)acrylate or (meth)acrylic acid (C2) having a phenyl group according to this embodiment include phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxy-polyethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, neopentyl glycol-(meth)acrylic acid-benzoic acid ester (meth)acrylate, benzyl (meth)acrylate, etc. From the viewpoint of the solubility of the elastomer, phenoxyethyl (meth)acrylate is preferred. Regarding the (meth)acrylate or (meth)acrylic acid (C2) according to the present embodiment, these (meth)acrylates or (meth)acrylic acids (C2) may be used alone or in combination of two or more kinds.

[0052] <(Meth)acrylate or (meth)acrylic acid having an alkylene oxide or siloxane unit (C3)> From the viewpoint of toughness, the (meth)acrylate or (meth)acrylic acid (C3) having an alkylene oxide or siloxane unit according to this embodiment has 4 to 15 alkylene oxide or siloxane units in its molecule, preferably 6 to 13. When the alkylene oxide or siloxane units are contained separately at two or more positions in the molecule, the total number of the alkylene oxide or siloxane units present at each position is 4 to 15, preferably 6 to 13. Moreover, the (meth)acrylate or (meth)acrylic acid (C3) having an alkylene oxide or siloxane unit according to this embodiment is more preferably polyfunctional from the viewpoints of toughness and curing speed.

[0053] Examples of (meth)acrylates (C3) having such an alkylene oxide or siloxane unit include bisphenol A alkylene oxide modified di(meth)acrylate, 2,2-bis(4-(meth)acryloxyphenyl)propane, 2,2-bis(4-(meth)acryloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxytetraethoxyphenyl)propane, and 2,2-bis(4-(meth)acryloxypolyethoxyphenyl)propane. From the viewpoint of curing speed, bisphenol A alkylene oxide modified di(meth)acrylate is preferred. Among the bisphenol A alkylene oxide modified di(meth)acrylates, bisphenol A EO (ethylene oxide) modified di(meth)acrylates are preferred. Among the bisphenol A alkylene oxide modified di(meth)acrylates, the compound of general formula (A) is preferred.

[0054] [ka]

[0055] (In formula (A), R1 and R1' represent a hydrogen atom or a methyl group. R1 and R1' may be the same or different. R2 and R2' represent an alkylene group. The alkylene group may have one hydroxyl group. R2 and R2' may be the same or different. R3 and R3' represent a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. R3 and R3' may be the same or different. p+q represents a number from 1 to 20. p and q may be the same or different.

[0056] In general formula (A), from the viewpoint of storage stability, it is preferable that R2 and R2' are alkylene groups not having a hydroxyl group. Among these, the following are preferred in terms of high resin strength. R1 and R1' are preferably methyl groups. R2 and R2' are preferably alkylene groups having 1 to 12 carbon atoms, more preferably ethylene groups. The alkylene groups preferably do not have hydroxyl groups. R3 and R3' are preferably methyl groups. p+q is a number of 1 to 20, preferably 5 to 15, and more preferably 10, from the viewpoint of the resin properties and flame resistance of the cured product. The (meth)acrylate or (meth)acrylic acid (C3) according to this embodiment may be used alone or in combination of two or more kinds.

[0057] <Acyclic polyfunctional (meth)acrylate or (meth)acrylic acid (C4)> Examples of the acyclic polyfunctional (meth)acrylate or (meth)acrylic acid (C4) according to this embodiment include trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. From the viewpoint of hardness adjustment, trimethylolpropane tri(meth)acrylate is preferred. The (meth)acrylate or (meth)acrylic acid (C4) according to this embodiment may be used alone or in combination of two or more kinds.

[0058] <Phosphate ester compound having (meth)acrylic group (C5)> Examples of the phosphoric acid ester compound having a (meth)acrylic group include phosphoric acid esters having a (meth)acrylic group. Examples of the phosphoric acid ester having a (meth)acrylic group include (2-hydroxyethyl)methacrylic acid phosphate, (meth)acryloyloxyethyl acid phosphate, dibutyl 2-(meth)acryloyloxyethyl acid phosphate, dioctyl 2-(meth)acryloyloxyethyl phosphate, diphenyl 2-(meth)acryloyloxyethyl phosphate, (meth)acryloyloxyethyl polyethylene glycol acid phosphate, and (meth)acryloyloxyethyl acid phosphate monoethanolamine half salt. These can be used alone or in combination.

[0059] <Monofunctional (meth)acrylate or (meth)acrylic acid in the first acrylic component (B) and the second acrylic component (C)> The two-part composition according to the present embodiment preferably contains a monofunctional (meth)acrylate or (meth)acrylic acid. In the present embodiment, the monofunctional (meth)acrylate or (meth)acrylic acid means a (meth)acrylate or (meth)acrylic acid having one (meth)acrylate group or one (meth)acrylic acid group in the molecule. The first acrylic component (B) may be contained as a monofunctional (meth)acrylate or (meth)acrylic acid, the second acrylic component (C) may be contained as a monofunctional (meth)acrylate or (meth)acrylic acid, and the first acrylic component (B) and the second acrylic component (C) may be contained as a monofunctional (meth)acrylate or (meth)acrylic acid. Preferably, from the viewpoint of the curing speed, at least the first acrylic component (B) is contained as a monofunctional (meth)acrylate or (meth)acrylic acid.

[0060] Examples of the monofunctional (meth)acrylate or (meth)acrylic acid according to the present embodiment include glycerin mono(meth)acrylate as the first acrylic component (B), and 2-hydroxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate as the second acrylic component (C). From the viewpoint of curing speed, one or more selected from the group consisting of glycerin mono(meth)acrylate, 2-hydroxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, and 3-hydroxypropyl (meth)acrylate are preferred. The monofunctional (meth)acrylate or (meth)acrylic acid according to the present embodiment may be used alone or in combination of two or more kinds.

[0061] In the two-part composition according to the present embodiment, the content of the monofunctional (meth)acrylate or (meth)acrylic acid in the first acrylic component (B) and the second acrylic component (C) is preferably 70 to 100 parts by mass, more preferably 75 to 90 parts by mass, when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass, from the viewpoint of curing speed. The content of the monofunctional (meth)acrylate or (meth)acrylic acid is specifically, for example, 70, 75, 80, 85, 90, 95, or 100 parts by mass, and may be within the range between any two of the numerical values ​​exemplified here. In addition, when a monofunctional (meth)acrylate or (meth)acrylic acid is used in combination, the content of the monofunctional (meth)acrylate or (meth)acrylic acid means the total amount of the monofunctional (meth)acrylate or (meth)acrylic acid used in combination.

[0062] <Polymerization initiator (D)> The two-part composition according to this embodiment contains a polymerization initiator (D). The polymerization initiator (D) according to this embodiment plays a role in curing the two-part composition. Examples of the polymerization initiator (D) according to the present embodiment include cumene hydroperoxide, benzoyl peroxide, t-butyl peroxybenzoate, t-butyloxyacetate, t-butyl peroxyisobutyrate, t-butyl peroxyphthalate, etc. From the viewpoints of curability and storage stability, cumene hydroperoxide is preferred. The polymerization initiator (D) according to the present embodiment may use these polymerization initiators (D) alone or in combination of two or more kinds.

[0063] In the two-part composition according to the present embodiment, the content of the polymerization initiator (D) is preferably 1 to 10 parts by mass, more preferably 3 to 7 parts by mass, when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass, from the viewpoint of curability and storage stability. The content of the polymerization initiator (D) is specifically, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 parts by mass, and may be within the range between any two of the numerical values ​​exemplified here. In addition, when the polymerization initiator (D) is used in combination, the content of the polymerization initiator (D) means the total amount of the polymerization initiator (D) used in combination.

[0064] <Condensation product of amine and aldehyde (E)> The two-dose composition according to the present embodiment contains an amine and aldehyde condensate (E). The amine and aldehyde condensate (E) according to the present embodiment is a condensate of any amine (alkylamine or arylamine) and any aldehyde, and may include not only a single structure but also a mixture or complex obtained as a result of condensation. An example of the amine and aldehyde condensate is an amine complex mixture obtained by condensing at least 1 mole, preferably 1.5 to 3 moles of aldehyde per mole of amine at 40 to 70°C in the presence of a carboxylic acid or an inorganic acid. Examples of the carboxylic acid or inorganic acid include propionic acid, phosphoric acid, and acetic acid, and examples of the amine and aldehyde include butylamine or aniline and butylaldehyde.

[0065] Examples of the condensate (E) of amine and aldehyde according to the present embodiment include a reaction condensate of butylamine or aniline and butylaldehyde, and aldehyde aniline. The aldehyde aniline according to the present embodiment means a reaction condensate of aldehydes and anilines. More specifically, n-butylaldehyde aniline is included. From the viewpoint of curing speed, n-butylaldehyde aniline is preferred. The amine and aldehyde condensate (E) according to the present embodiment may be used alone or in combination of two or more kinds.

[0066] In the two-part composition according to the present embodiment, the content of the amine and aldehyde condensate (E) is preferably 5 to 40 parts by mass, more preferably 10 to 30 parts by mass, when the total of the third acrylic component (F), the amine and aldehyde condensate (E) and the reducing agent (G) is 100 parts by mass, from the viewpoint of curing speed. The content of the amine and aldehyde condensate (E) is specifically, for example, 5, 10, 15, 20, 25, 30, 35, or 40 parts by mass, and may be within a range between any two of the numerical values ​​exemplified here. In addition, when the amine and aldehyde condensate (E) is used in combination, the content of the amine and aldehyde condensate (E) means the total amount of the amine and aldehyde condensate (E) used in combination and the amine and aldehyde condensate (E) used in combination, not only the single structure, but also the mixture or composite obtained as a result of condensation.

[0067] <Third acrylic component (F)> The two-part composition according to this embodiment contains a third acrylic component (F) in the second part. Examples of the third acrylic component (F) according to this embodiment include those exemplified in the first acrylic component (B) and the second acrylic component (C) used in the first part. The third acrylic component (F) according to the present embodiment may be used alone or in combination of two or more of these third acrylic components (F), and may be the same as or different from the first acrylic component (B) and the second acrylic component (C) used in the first agent. From the viewpoint of low volatility and coatability, one or more selected from the group consisting of phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, neopentyl glycol-(meth)acrylic acid-benzoic acid ester (meth)acrylate, and benzyl (meth)acrylate are preferred.

[0068] <Fluorine-containing (meth)acrylate or Fluorine-containing (meth)acrylic acid (F1)> The two-part polymerizable composition according to the present embodiment preferably contains a fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid (F1) in the third acrylic component (F) from the viewpoint of lowering the surface tension of the liquid and improving the wettability to the adherend. The fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid means a (meth)acrylate or (meth)acrylic acid having one or more fluorine atoms in the molecule. The fluorine-containing (meth)acrylate (F1) according to the present embodiment is preferably a fluorine-containing (meth)acrylate containing a fluorinated alkyl group, and more preferably contains difluoromethylene (-CF2-). Examples of the acrylate include monofunctional (meth)acrylates such as 1H,1H,2H,2H-tridecafluorooctyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, and 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl (meth)acrylate, and polyfunctional (meth)acrylates such as 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9-hexadecafluoro-1,10-decane di(meth)acrylate, of which 1H,1H,2H,2H-tridecafluorooctyl (meth)acrylate is most preferred in terms of wettability to the adherend and storage stability. The fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid (F1) according to the present embodiment may be used alone or in combination of two or more kinds. By adding the fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid (F1), the second agent is expected to have an effect of improving the wetting and spreading properties when applied to an adherend, thereby improving the applicability.

[0069] In the two-part composition according to the present embodiment, the content of the fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid (F1) is preferably 0.001 to 3 parts by mass, more preferably 0.5 to 2 parts by mass, when the total of the third acrylic component (F) is 100 parts by mass, from the viewpoint of reducing the surface tension of the adhesive liquid and improving the wettability of the adherend to improve workability. The content of the fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid (F1) is specifically, for example, 0.001, 0.5, 1.0, 1.5, 2.0, or 3.0 parts by mass, and may be within the range between any two of the numerical values ​​exemplified here. In addition, when the fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid (F1) is used in combination, the content of the fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid (F1) means the total amount of the fluorine-containing (meth)acrylate or fluorine-containing (meth)acrylic acid (F1) used in combination.

[0070] <Reducing Agent (G)> The two-part polymerizable composition according to the present embodiment contains a reducing agent (G). The reducing agent (G) according to the present embodiment includes those capable of generating radicals by reacting with the polymerization initiator (D) used in the first part. Specifically, at least one selected from the group consisting of tertiary amines, thiourea derivatives, and transition metal salts is more preferable. Examples of thiourea derivatives include acetylthiourea and ethylenethiourea. Examples of transition metal salts include cobalt naphthenate, cobalt octylate, copper naphthenate, copper neodecanoate, and vanadyl acetylacetonate. From the viewpoints of curing speed, toughness of the adhesive cured product, and heat cycle resistance, transition metal salts are preferable. As the transition metal salt, at least one selected from the group consisting of copper naphthenate and copper neodecanoate is preferable, and copper neodecanoate is more preferable. The reducing agent (G) according to the present embodiment may be used alone or in combination of two or more of these reducing agents (G).

[0071] In the two-part composition according to the present embodiment, the content of the reducing agent (G) is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 1 part by mass, when the total of the third acrylic component (F), the condensate of amine and aldehyde (E) and the reducing agent (D) is 100 parts by mass, from the viewpoint of curing speed. The content of the reducing agent (G) is specifically, for example, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 1.0, 2.0, 3.0, 4.0, or 5.0 parts by mass, and may be within the range between any two of the numerical values ​​exemplified here. In addition, when the reducing agent (G) is used in combination, the content of the reducing agent (G) means the total amount of the reducing agent (G) used in combination.

[0072] <Stabilizer (H)> The two-part polymerizable composition according to the present embodiment preferably further contains a stabilizer (H) in the second part. By further containing a stabilizer (H) in the second part, it is possible to prevent the viscosity of the second part from increasing during storage. This is believed to be because the stabilizer (H) prevents the viscosity from increasing due to the polymerization of the third acrylic component (F) caused by radicals generated by the amine and aldehyde condensate (E) accelerating the oxidation-reduction reaction between the reducing agent (D) and oxygen during storage.

[0073] In the two-part composition according to the present embodiment, the content of the stabilizer (H) is preferably 0.001 to 0.5 parts by mass when the total of the amine and aldehyde condensate (E), the third acrylic component (F), and the reducing agent (G) is 100 parts by mass, from the viewpoint of storage stability and curing speed. If the content is 0.001 parts by mass or more, the storage stability is improved, and if the content is 0.5 parts by mass or less, the curing speed is improved. The content of the stabilizer (H) is more preferably 0.05 to 0.4 parts by mass, and even more preferably 0.1 to 0.3 parts by mass, from the viewpoint of storage stability and curing speed, and specifically, for example, 0.001, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, or 0.5 parts by mass, and may be within the range between any two of the numerical values ​​exemplified here. In addition, when the stabilizer (H) is used in combination, the content of the stabilizer (H) means the total amount of the stabilizer (H) used in combination.

[0074] The stabilizer (H) is not particularly limited as long as it is a known stabilizer, polymerization inhibitor, or antioxidant. Examples of the stabilizer (H) include quinone stabilizers such as methylhydroquinone, hydroquinone, 2,2-methylene-bis(4-methyl-6-tertiarybutylphenol), catechol, hydroquinone monomethyl ether, monotertiarybutylhydroquinone, 2,5-ditertiarybutylhydroquinone, p-benzoquinone, 2,5-diphenyl-p-benzoquinone, and 2,5-ditertiarybutyl-p-benzoquinone; azine stabilizers such as phenothiazine; citric acid, picric acid, and the like. Phosphoric acid, tert-butylcatechol, 4-methoxyphenol, 2-butyl-4-hydroxyanisole, 2,6-ditert-butyl-p-cresol, ammonium salt of N-nitroso-N-phenylhydroxylamine, tetrakis[methylene-3(3'5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, 3,9-bis[2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane, Kan, (meth)acrylic acid 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl, 2,2'-thiodiethyl bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N-ocladecyl-3(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, N,N'-hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanamide, 3-(4-hydroxy-3,5-diisopropylphenyl) octyl propionate, 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)mesitylene, 2,4-bis(dodecylthiomethyl)-6-methylphenol, calcium bis[3,5-di(tert-butyl)-4-hydroxybenzyl(ethoxy)phosphinate], 2,4-bis(octylthiomethyl)-6-methylphenol, bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionic acid][ethylenebis(oxyethylene)], 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanate, bis[4-(1,1,3,3-tetramethylbutyl)phenyl]amine, 4-[[4,6-bis(octylthio)-1,3,5-triazin-2-yl]amino]-2,6-di-tert-butylphenol, 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid diethyl ester, 1,3,5-tris[[4-(1,1- hindered phenol antioxidants such as dimethylethyl)-3-hydroxy-2,6-dimethylphenyl]methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione; and stable radical type compounds having stable radicals such as 1-oxyl-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl. In particular, stable radical type compounds are preferred in terms of storage stability. As the stable radical type compound, at least one selected from the group consisting of 1-oxyl-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl is preferred. Stable radical type compounds having a nitroxide radical as a stable radical are more preferred. Specifically, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl is most preferred. The stabilizer (H) may be used alone or in combination of two or more kinds.

[0075] <Viscosity of the first agent> From the viewpoint of workability (applicability of the adhesive), the viscosity of the first part of the two-part composition according to this embodiment is preferably 1,000 to 100,000 mPa·s, and more preferably 1,000 to 50,000 mPa·s. The viscosity of the first part referred to here is the viscosity of a composition containing the elastomer (A), the first acrylic component (B), the second acrylic component (C), and the polymerization initiator (D).

[0076] The viscosity of the first agent in this embodiment is measured at 25° C. in accordance with JIS K7117-1.

[0077] <Viscosity of the second agent> In the two-part composition according to this embodiment, from the viewpoint of improving the applicability to an adherend, the viscosity of the second part is preferably 1 to 1000 mPa·s, and more preferably 5 to 100 mPa·s.

[0078] The viscosity of the second agent according to this embodiment is measured at 25° C. in accordance with JIS K7117-1.

[0079] <Composition of 1st and 2nd agents> In the two-part composition of this embodiment, when the total of the first and second parts is 100 parts by mass, the ratio of the first part:the second part is preferably 50 to 98:2 to 50 parts by mass, and more preferably 80 to 95:5 to 20 parts by mass. From the viewpoint of heat cycle resistance, the two-part composition according to this embodiment preferably contains 55 to 100 parts by mass of elastomer (A) in the first part, more preferably 80 to 100 parts by mass, and even more preferably 95 to 100 parts by mass of elastomer (A) in the second part, when the total amount of elastomer (A) in the first part and elastomer (A) in the second part is taken as 100 parts by mass. In one embodiment, it is preferable that elastomer (A) is contained substantially only in the first part.

[0080] <Adhesive> The two-component composition according to this embodiment can be made into an adhesive by adding additives such as a polymerization inhibitor, a stabilizer, an antioxidant, and an ultraviolet absorber, as necessary.

[0081] <zygote> A bonded body can be obtained by applying the composition according to this embodiment to an adherend and bonding the adherend.

[0082] The bonded body of this embodiment can be obtained, for example, by applying a first agent to one of the adherend surfaces or adherends, applying a second agent to the other of the adherend surfaces or adherends, and then joining these two adherend surfaces or adherends together.

[0083] In the above embodiment, the material of the adherend may be, but is not limited to, iron, plated surfaces, etc. The adhesive composition exhibits excellent adhesion, particularly to iron and plated surfaces, and is therefore suitable for use with ferrite magnets, plated products, etc.

[0084] The composition according to the present embodiment is capable of bonding adherends together in an extremely short time, and therefore can achieve rapid curing. The composition according to the present embodiment also has excellent heat cycle resistance. Therefore, the composition according to the present embodiment is suitable as an adhesive for manufacturing products that require fast curing and are expected to be used in environments ranging from low to high temperatures, such as from −40 to 100° C. Examples of such products include speakers, motors, power transformers, etc. EXAMPLES

[0085] The present invention will be described in more detail below with reference to examples. However, these are merely examples and the present invention is not limited to these.

[0086] <Raw materials used> [Elastomer (A)] Liquid NBR (product name: 1300X33LC VTBNX, manufactured by HUNTSMAN, methacrylic-terminated NBR, nitrile content is 18 parts by mass per 100 parts by mass of NBR, viscosity 250,000 mPa s) ·Solid NBR (Product name: N-230SV, manufactured by JSR, nitrile content is 30 to 35 parts by mass in 100 parts by mass of NBR) -Butadiene rubber (product name: BR01, manufactured by JSR Corporation) Core-shell type graft copolymer (product name: BL-20, manufactured by Denka Co., Ltd., contains 15 parts by mass of methyl methacrylate, 47 parts by mass of butadiene, and 38 parts by mass of other vinyl monomers out of a total of 100 parts by mass of MBAS polymer, methyl methacrylate, butadiene, and other vinyl monomers) [First acrylic component (B)] Glycerin monomethacrylate (product name: Blenmar GLM, manufactured by NOF Corporation) [Second acrylic component (C)] 2-Hydroxyethyl methacrylate (product name: 2HEMA, manufactured by Mitsubishi Gas Chemical Co., Ltd.) Phenoxyethyl methacrylate (product name: M141, manufactured by MIWON) Bisphenol A EO modified dimethacrylate (product name: BPE-500, manufactured by Shin-Nakamura Chemical Co., Ltd., 2,2-bis(4-(methacryloxypolyethoxy)phenyl)propane, in the above general formula (A), R1 and R1' are methyl groups, R2 and R2' are ethylene groups, R3 and R3' are methyl groups, and p+q=10) Methacrylic acid (product name: GE-110, manufactured by Mitsubishi Gas Chemical Co., Ltd.) (2-Hydroxyethyl) methacrylate acid phosphate (product name: JPA-514 manufactured by Johoku Chemical Industry Co., Ltd.) [Polymerization initiator (D)] Cumene hydroperoxide (product name: PH-80, manufactured by NOF Corporation) [Condensation product of amine and aldehyde (E)] n-Butylaldehyde aniline (product name: NX-8, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) [Third acrylic component (F)] Phenoxyethyl methacrylate (product name: PO, manufactured by Kyoeisha) 1H,1H,2H,2H-Tridecafluorooctyl acrylate (product name: Viscoat 13F, manufactured by Osaka Organic Chemical Industry Co., Ltd.) [Reducing agent (G)] Copper neodecanoate (product name: Copper neodecanoate, manufactured by Nippon Chemical Industries Co., Ltd.) [Stabilizer (H)] 4-Hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl (generic name: Tempol, manufactured by Tokyo Chemical Industry Co., Ltd.) 4-Methoxyphenol (product name: MQ-F, manufactured by Kawaguchi Chemical Industry Co., Ltd.) p-Benzoquinone (product name: PBQ, manufactured by Seiko Chemical Co., Ltd.)

[0087] <Examples 1 to 20 and Comparative Examples 1 to 6> The first part was prepared by mixing the elastomer (A), the first acrylic component (B), the second acrylic component (C), and the polymerization initiator (D) in the ratios shown in Table 1. The second part was prepared by mixing the amine and aldehyde condensate (E), the third acrylic component (F), the reducing agent (G), and the stabilizer (H) in the ratios shown in Table 1. An adhesive consisting of the first and second parts was prepared. The first and second parts were mixed in a mass ratio of 9:1.

[0088] The adhesive consisting of the first and second parts containing the above additives was used to measure the setting time of the adhesive obtained and the impact resistance of the cured product after exposure to heat cycles, using the methods described below.

[0089] <Measurement of adhesion time> Test pieces for measuring tensile shear adhesive strength were prepared in accordance with JIS K6850. The first agent containing the additive was applied to one of the test pieces for measuring the tensile shear adhesive strength, and the second agent was applied to the other test piece, and the coated surfaces of each adherend were brought together and bonded together. The tensile shear adhesive strength of the test pieces 20 seconds after bonding was measured using a push-pull gauge. The tensile shear adhesive strength was evaluated according to the following evaluation criteria and used as an index of rapid curing. A: Tensile shear adhesive strength is 0.05 MPa or more B: Tensile shear adhesive strength is 0.03 MPa or more and less than 0.05 MPa C: Tensile shear adhesive strength is less than 0.03 MPa

[0090] <Impact resistance of cured body after heat cycle exposure> A ferrite magnet / iron plate was bonded as an adherend by the above-mentioned coating method to prepare a test specimen for heat cycle exposure. The test piece for heat cycle exposure was exposed to a heat cycle of heating from -40°C to 110°C at 2°C / min and cooling from 110°C to -40°C at 2°C / min, repeated 50 times. After exposure, the test pieces were dropped from a height of 1m to conduct an impact resistance test. The impact resistance of the cured product after exposure to heat cycles was evaluated according to the following evaluation criteria, and used as an index of heat cycle resistance. A: The test piece did not peel off even after 30 impact tests. B: The test piece peeled off after 21 to 29 impact tests. C: The test piece peeled off after 11 to 20 impact tests. D: The test piece peeled off after 10 or fewer impact tests.

[0091] <Viscosity of the first agent> The viscosity of the first agent was measured at 25°C in accordance with JIS K7117-1.

[0092] <Viscosity of the second agent> The viscosity of the second part was measured at 25°C in accordance with JIS K7117-1.

[0093] <Storage stability (second agent)> 10 g of the second part was weighed into a 20 ml vial (made of glass) and exposed to an atmosphere of 60°C for 14 days. After that, the viscosity was measured at 25°C in accordance with JIS K7117-1, and the viscosity increase rate was calculated using the following formula. Viscosity increase rate (%) = (viscosity after 14 days of exposure / viscosity before 14 days of exposure) x 100

[0094] The above results are shown in Tables 1 to 4. In the tables, the content of each component is expressed in parts by mass. The nitrile content of NBR is the content (parts by mass) of (meth)acrylonitrile monomer units in 100 parts by mass of NBR. In addition, "content of B in A" means the content of B contained in 100 parts by mass of A.

[0095] [Table 1]

[0096] [Table 2]

[0097] [Table 3]

[0098] [Table 4]

[0099] As can be seen from the results of Tables 1 to 4, the adhesives using the compositions according to the examples are found to be excellent in fast curing properties and impact resistance after exposure to heat cycles. On the other hand, the adhesives using the compositions according to the comparative examples are found to be inferior in one or more aspects of fast curing properties and impact resistance after exposure to heat cycles. It is also found that the addition of a stabilizer to the second agent can further achieve the effect of suppressing viscosity increase during storage. [Industrial Applicability]

[0100] The adhesive using the composition according to the present invention has excellent fast curing properties and heat cycle resistance. The composition according to the present invention can be suitably used as an adhesive in the manufacture of products that require fast curing properties and are expected to be used in high-temperature environments, for example, and has industrial applicability.

Claims

1. Consists of a first agent and a second agent, The first agent contains an elastomer (A), a first acrylic component (B), a second acrylic component (C), and a polymerization initiator (D), The second agent contains an amine and aldehyde condensate (E), a third acrylic component (F), and a reducing agent (G), The elastomer (A) is at least one selected from the group consisting of nitrile butadiene rubber (NBR), butadiene rubber, and core-shell type graft copolymers, The first acrylic component (B) is a (meth)acrylate containing two or more hydroxyl groups bonded to carbon atoms in one molecule, the second acrylic component (C) is a (meth)acrylate or (meth)acrylic acid other than the first acrylic component (B); the third acrylic component (F) is a (meth)acrylate; The reducing agent (G) is a transition metal salt, The content of the elastomer (A) is 30 to 70 parts by mass when the total amount of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass. A two-part composition.

2. 2. The composition of claim 1, wherein the condensate of an amine and an aldehyde (E) is an aldehyde aniline.

3. The composition according to claim 1 or claim 2, wherein the content of the first acrylic component (B) is 10 to 40 parts by mass when the total amount of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass.

4. The composition according to claim 1 or claim 2, wherein a content of the monofunctional (meth)acrylate or (meth)acrylic acid in the first acrylic component (B) and the second acrylic component (C) is 70 to 100 parts by mass when a total amount of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass.

5. The composition according to claim 1 or 2, wherein one or more of the elastomer components contained in the elastomer (A) is a liquid elastomer (A1) that is liquid at a temperature of 23° C.

6. The composition according to claim 1 or claim 2, wherein the elastomer (A) contains one or more nitrile butadiene rubbers (NBR).

7. The composition of claim 6, wherein the one or more NBRs contain two or more nitrile butadiene rubbers (NBRs) having different nitrile contents.

8. The composition according to claim 1 or claim 2, wherein the nitrile content in the elastomer (A) is 0.001 to 0.300 parts by mass per 100 parts by mass of the elastomer (A).

9. The composition according to claim 1 or claim 2, wherein the elastomer (A) contains a core-shell type graft copolymer (A2), and the content of the core-shell type graft copolymer (A2) is 0 to 10 parts by mass when the total of the first acrylic component (B) and the second acrylic component (C) is 100 parts by mass.

10. The composition according to claim 1 or claim 2, wherein the elastomer (A) contains a (meth)acryloyl-modified elastomer (A3).

11. The composition according to claim 1 or claim 2, wherein the first agent has a viscosity of 1,000 to 100,000 mPa·s at 25°C.

12. The composition according to claim 1 or claim 2, comprising 0.001 to 3 parts by mass of a fluorine-containing (meth)acrylate or a fluorine-containing (meth)acrylic acid (F1) per 100 parts by mass of the third acrylic component (F).

13. The composition according to claim 1 or claim 2, further comprising a stabilizer (H) in the second agent.

14. The composition according to claim 13, wherein a content of the stabilizer (H) is 0.001 to 0.5 parts by mass when a total content of the amine and aldehyde condensate (E), the third acrylic component (F), and the reducing agent (G) is 100 parts by mass.

15. The composition according to claim 13, wherein the stabilizer (H) comprises a stable radical type compound having a stable radical.

16. The composition according to claim 15, wherein the stable radical of the stable radical type compound is a nitroxide radical.

17. The composition according to claim 15, wherein the stable radical type compound comprises at least one selected from the group consisting of 1-oxyl-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl.

18. An adhesive comprising the composition according to claim 1 or 2.

19. An adhesive for a speaker, comprising the composition according to claim 1 or 2.

20. A motor adhesive containing the composition described in claim 1 or claim 2.

21. A bonded body obtained by bonding with the composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Improving method of energy efficiency in isotope separation by laser

    JP1978041699A

  • Two-part liquid type acrylic adhesion composition

    JP1990178374A

  • Adhesive composition, bonding method, bonded form, and method for producing bonded form

    JP2009197160A

  • Adhesive composition, cured product thereof and conjugate

    JP2015030748A

  • Composition

    JP2015218200A